Revitalisasi Usaha Tradisional Menggunakan Teknologi Advanced Dough Mixer Kerupuk Tengiri Untuk Kualitas Yang Konsisten dan Higienis - Mas Ahmad Baihaqi; Alief Muhammad; Raihan Wishal Nafis; Hartawan Abdillah; Tamam Asrori (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
The revitalization program for traditional mackerel cracker businesses in Probolinggo City has successfully improved production capacity through the implementation of Advanced Dough Mixer technology. This technology replaced the manual mixing method, increasing production efficiency by 50% while ensuring product consistency and hygiene. Additionally, e-finance and digital marketing training was provided to the partners to enhance financial management and expand market access through e-commerce platforms. The results of this program showed a significant increase in the partner’s production capacity, from 7 kg per day to 10-12 kg per day. Digital marketing efforts also boosted sales by 50% through online stores. This program not only improved the quality of mackerel crackers but also opened broader market opportunities and directly contributed to the improvement of the local economy. The participation of students in this activity also contributed to the development of technical and entrepreneurial skills relevant to the Merdeka Belajar Kampus Merdeka (MBKM) program framework